2021
DOI: 10.3348/jksr.2020.0155
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Ductal Carcinoma Originating from a Borderline Phyllodes Tumor in a Young Female: A Case Report

Abstract: 유방 엽상종양은 전체 유방 종양의 1% 미만을 차지하는 드문 섬유상피종양이다. 엽상종양은 유관주위 버팀질 세포에서 기원하여 상피 성분과 버팀질 성분을 모두 포함하는 특징을 가지며, 조직학적으로 양성, 경계성, 악성으로 구분된다. 엽상종양의 상피 성분에서 암이 발생하는 것은 매우 드물기 때문에 이에 대한 영상의학적 소견은 명확히 정립된 바가 없다. 이에 저자들은 21세 젊은 여성에서 경계성 엽상종양 내에서 생긴 침윤성 유관암을 경험하였기에 자기공명영상을 포함한 영상의학적 소견과 조직병리학적 소견을 보고하고자 한다.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ninety-eight cases of in situ or invasive carcinoma within a PT were identified in the literature [3‒64], including 31 cases compiled from case series by Sin et al, Widya et al, Co M. et al, Saimura et al, and Nistor-Ciurba et al [65‒69], as shown in Table 1. Patients averaged 49 years old, ranging from 19 to 80 years.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-eight cases of in situ or invasive carcinoma within a PT were identified in the literature [3‒64], including 31 cases compiled from case series by Sin et al, Widya et al, Co M. et al, Saimura et al, and Nistor-Ciurba et al [65‒69], as shown in Table 1. Patients averaged 49 years old, ranging from 19 to 80 years.…”
Section: Resultsmentioning
confidence: 99%